Pemanfaatan Library 2.0 di Perpustakaan Perguruan Tinggi di Indonesia: Studi Kasus 150 Universitas terbaik di Indonesia versi Webometrics tahun 2016 - Muhammad Usman Noor (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2018)
Library 2.0 is a library of services that always make user-oriented changes by inviting users to participate in service creation. Conditions of application of Library 2.0 in Indonesia results from Research-research on the implementation of Library 2.0 in Indonesia has begun in the year 2000an. In general, the application of Library 2.0 in Indonesia from previous research results is still less developed. Utilization of Library 2.0 applications can be divided into four main categories, namely information push / pull, information retrieval, information exchange and social networking. The purpose of this research is to measure the application of Library 2.0 in 172 Academic Library of Indonesia by Webometric version of 2016. This research uses library research in collecting data through survey method. As a result, social networking became the most widely used Library 2.0 application in the academic library of Indonesia with 44.04% percentage, then Information push / pull with 30.66%, Information exchange of 20.15% and the lowest information retrieval with 11.62%. This shows that there is a high utilization in some categories of Library 2.0 application utilization in Indonesian Academic Library.Library 2.0 adalah konsep perpustakaan yang mengedepankan aspek pengguna dalam memberikan pelayanannya. Pengguna turut aktif berpartisipasi dalam penyelenggaraan layanan perpustakaan. Kondisi penggunaan Library 2.0 di Indonesia dari berbagai penelitian sebelumnya mengatakan bahwa Library 2.0 masih belum berkembang. Penggunaan konsep Library 2.0 dapat dibedakan menjadi 4 kategori utama, tarikan/dorongan informasi, penemuan kembali informasi, pertukaran informasi, dan jejaring sosial. Tujuan dari penelitian ini adalah untuk mengukur penggunaan Library 2.0 dari 172 perpustakaan akademik di Indonesia berdasarkan ranking Webometric. Penelitian ini menggunakan data primer melalui metode survey. Hasil dari penelityian ini, jejaring sosial menjadi penerapan konsep Library 2.0 terbanyak dengan nilai 44.04% dari total responden, diikuti tarikan/dorongan informasi dengan 30.66%, pertukaran informasi 20.15% dan terakhir penemuan kembali informasi dengan nilai 11.62%. Hal ini menunjukkan bahwa terdapat penggunaan Library 2.0 yang tinggi dalam beberapa kategori dalam penyelenggaran layanan perpustakaan di perpustakaan akademik di Indonesia.